More Is Not Always Better: The Case of Counterterrorism Security. (September 2019) - Dev, Pritha; Grabiszewski, Konrad
Can counterterrorism security be counterproductive? We argue that it can be when the at-risk population acts strategically. We model a two-stage game where the government first chooses the defensive security level for a public place. The second stage is a simultaneous-move game with terrorist choosing terror effort and members of the population deciding whether or not to attend the public place. Our key measure of the efficiency of the counterterrorism security is the expected number of casualties. Under very standard and general assumptions, we show that it is possible that more security leads to an increase in that number. This is because increasing security both discourages and encourages the terrorist. On the one hand, more security makes a successful terror attack less likely (discouragement). On the other hand, more security motivates more people to attend the public place which makes the attack more valuable to the terrorist (encouragement).